The new indication of TEVAR for uncomplicated type B aortic dissection. Issue 25 (June 2016) - Song, Chao; Lu, Qingsheng; Zhou, Jian; Yu, Guanyu; Feng, Xiang; Zhao, Zhiqing; Bao, Junmin; Feng, Rui; Jing, Zaiping
Abstract : Abstract: The classical therapeutic indication for type B aortic dissection is based on either medication or open surgery; medication therapy is recommended for relatively stable uncomplicated type B aortic dissection. With improvements in endovascular repair and the potential risk of disease progression, it is now necessary to evaluate the requirement for revision of the therapeutic choice of uncomplicated type B aortic dissection based on morphological features and time window. Data from 252 patients diagnosed as uncomplicated type B aortic dissection from 1992 to 2015 were analyzed retrospectively. Among these cases, 117 patients received medication therapy and 135 patients underwent endovascular repair. The 60-month survival rate in the endovascular group was higher than that in the medication group (92.3% vs 67.6%). According to the morphological evaluation, visceral artery involvement and false/true lumen ratios over 0.7 were strong risk factors for medical treatment alone. Increased surgical time and blood loss were found in patients treated in the chronic phase, compared with those who underwent endovascular repair within 14 days of the onset of symptoms. With improvements in aortic remodeling techniques, endovascular repair has been shown to improve long-term survival rates of patients with uncomplicated aortic dissection. Considering the potential risk of death, we recommend that patients with visceral artery involvement and a false/true lumen ratio over 0.7 should receive endovascular repair aggressively. Furthermore, delayed endovascular repair in the chronic phase does not improve the long-term outcome of uncomplicated type B aortic dissection.